2012
DOI: 10.1063/1.3702448
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic structure and magnetization process of the glass-coated Fe-based amorphous microwire

Abstract: Articles you may be interested inMagnetic field and mechanical stress tunable microwave properties of composites containing Fe-based microwires Appl. Phys. Lett.Size triggered change in the magnetization mechanism of nearly zero magnetostrictive amorphous glass-coated microwires Stress induced magnetic anisotropy and giant magnetoimpedance in Fe-rich glass-coated magnetic microwires Magnetic structure of amorphous Fe 73,9 B 13,2 Si 10,9 C 2 microwires was studied. The magnetic structure of the as-prepared micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 15 publications
(14 reference statements)
1
16
0
Order By: Relevance
“…black part of magnetic contrast disappearing over a total length of around 120 μm (apparent surface domain wall length). Such tilted surface domain wall structure could be attributed to the tilted domain wall, which was previously predicted and observed in glass-coated microwires [20]- [22]. This tilted surface structure of the domain wall was observed along the entire length of 2 cm piece of the sample.…”
Section: Domain Wall Trapped In Potential Wellsupporting
confidence: 76%
“…black part of magnetic contrast disappearing over a total length of around 120 μm (apparent surface domain wall length). Such tilted surface domain wall structure could be attributed to the tilted domain wall, which was previously predicted and observed in glass-coated microwires [20]- [22]. This tilted surface structure of the domain wall was observed along the entire length of 2 cm piece of the sample.…”
Section: Domain Wall Trapped In Potential Wellsupporting
confidence: 76%
“…Additionally, strong circular anisotropy is induced during current annealing which also leads to the increase of thickness of outer shell that consists of many adjacent strips with different orientation of magnetization (radial and circular ones) as is schematically depicted in Fig. 1, which has been experimentally observed in amorphous microwires, see for example in [13,14]. As a result of such annealing thickness of outer shell almost linearly increases while values of the switching field exhibit slightly decreasing tendency.…”
Section: Resultsmentioning
confidence: 87%
“…It was shown earlier [2] that the domain structure of CGC MNW can be presented schematically as two domains that are separated by a 180° wall in the form of a cylin drical surface. However, in [12], another model is pro posed by the authors based on magneto optic mea surements that contradicts (as will be shown below) a number of experimental facts and theoretical conclu sions. Regardless of the accepted magnetic model, but in the framework of one of them, there are two mech anisms of deceleration of the domain wall.…”
Section: Introductionmentioning
confidence: 99%
“…One of them is described in [6,7] and the other in [10,11]. The theoretical justifications of the magnetic model in [12] and the mechanisms of the domain wall decelera tion in [10,11] are partially based on incorrect calcu lations of the residual stresses. This fact has already been mentioned in [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation